Patient characteristics and risk factors contributing to disease progression among hospitalised patients with Covid-19: lesson from Malaysia - Othman, Nurul Syafiqah; Mohd. Zin, Che Suraya; Mohd Taufek, Nor Hidayah (IIUM Press, 2023)
Background: Patients who were hospitalised with severe COVID-19 infection could progress to severe conditions due to various factors, whereas some patients may recover to mild conditions quickly. There was limited information regarding characteristics and factors affecting disease progression in this population in Malaysia. This study aimed to investigate patient characteristics and risk factors contributing to disease progression among COVID-19 patients during hospitalisation. Methods: A retrospective cross-sectional study using electronic medical record data from COVID-19 patients admitted to two public hospitals in East Coast Malaysia from February 2020 to August 2021 was conducted. This study included patients with asymptomatic or mild condition (stage 1 – stage 3) upon hospital admission and progressed to severe condition (stage 4 – stage 5) during hospitalisation. Results: A total of 163 patients were included (57% male) with the age of (mean±SD, 62.3 ±14.0 years). Multivariable logistic regression associated with COVID-19 disease progression included elderly (OR, 1.06; 95% CI, 1.04, 1.08; p = ≤0.05), diabetes mellitus (OR, 2.27; 95% CI, 1.27, 4.06; p = 0.006), chronic kidney disease (OR, 4.87; 95% CI, 1.92, 12.38; p=0.001), and presented with more than three COVID-19 symptoms (OR, 9.80; 95% CI, 6.08-15.81, p = ≤0.05). Conclusion: Risk factors for COVID-19 disease progression included elderly patients, comorbidities of diabetes mellitus, chronic kidney disease or more than three COVID-19 symptoms. Close monitoring and early intervention should be implemented for these patients to prevent the disease progression and poor prognosis.